Analisis Pekerja Migran Pada Sektor Formal Dan Informal - Rafifah; Isra Yeni (Media Riset Ekonomi Pembangunan (MedREP), 2024)
This research was conducted to identify opportunities for migrant workers the formal and informal work sectors in Riau Islands. The method used in this research is binary logistic regression with the object of the research is the entire labor force working in Riau Islands in August 2022 period with data obtained from the National Labor Force Survey (SAKERNAS), which is processed using STATA 14 software. Based on the analysis that has been carried out based on the regression result of 5133 samples as a whole, the partial results show that the status of upward migration has a positive and insignificant effect, in other words it has no effect on labor opportunities in the formal and informal work sectors in Riau Islands, while education gender have a positive and significant effect on labor opportunities in the formal and informal works sectors, age, and marriage status have a negative and significant effect on labor opportunities in the formal and informal work sectors.